2015
DOI: 10.1103/physrevb.91.060508
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductivity stabilized by electron-hole interband coupling in collapsed tetragonal phase ofKFe2As2under high pressure

Abstract: We report a high-pressure study of simultaneous low-temperature electrical resistivity and Hall effect measurements on high quality single-crystalline KFe2As2 using designer diamond anvil cell techniques with applied pressures up to 33 GPa. In the low pressure regime, we show that the superconducting transition temperature Tc finds a maximum onset value of 7 K near 2 GPa, in contrast to previous reports that find a minimum Tc and reversal of pressure dependence at this pressure. Upon applying higher pressures,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
8
25
0
Order By: Relevance
“…It is intriguing to notice that the same phase transition with disappearance of the holelike FS at Γ that here produces a dramatic increase of the coupling in both bands seems to be responsible for the high- T c phase at 47 K observed in rare-earth doped CaFe 2 As 2 47, and for the second, higher- T c superconducting dome in LaFeAsO 1− x H x 48. Recently, a study of KFe 2 As 2 in an extended pressure range (up to 30 GPa) has shown two superconducting phases in the phase diagram49. A first superconducting dome (with a maximum around 2.5 GPa) occurs in the T structure, and is extended up to about 7 GPa.…”
Section: Discussionmentioning
confidence: 60%
“…It is intriguing to notice that the same phase transition with disappearance of the holelike FS at Γ that here produces a dramatic increase of the coupling in both bands seems to be responsible for the high- T c phase at 47 K observed in rare-earth doped CaFe 2 As 2 47, and for the second, higher- T c superconducting dome in LaFeAsO 1− x H x 48. Recently, a study of KFe 2 As 2 in an extended pressure range (up to 30 GPa) has shown two superconducting phases in the phase diagram49. A first superconducting dome (with a maximum around 2.5 GPa) occurs in the T structure, and is extended up to about 7 GPa.…”
Section: Discussionmentioning
confidence: 60%
“…The phase diagram of the 122 system is similar to that of the 122* system37. The DFT calculations showed the change in the electronic structure between the T phase and cT phase38.…”
Section: Discussionmentioning
confidence: 61%
“…External pressure changes the superconducting properties of the K122 tetragonal phase. T c shows a nonmonotonic behavior on pressure [11,12,[22][23][24][25], with a minimum at p c ∼ 1.8 GPa [25]. Around this point, T c shows a universal V-shape dependence in the weak pressure regime [26], what has been reported not only in the case of K122 [25], but also for Rb122 [26] and Cs122 [27].…”
Section: Introductionmentioning
confidence: 67%